2021
DOI: 10.1021/acsami.0c21440
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature 2D/2D Ohmic Contacts in WSe2 Field-Effect Transistors as a Platform for the 2D Metal–Insulator Transition

Abstract: We report the fabrication of hexagonal-boron-nitride (hBN) encapsulated multiterminal WSe 2 Hall bars with 2D/2D low-temperature Ohmic contacts as a platform for investigating the two-dimensional (2D) metal-insulator transition. We demonstrate that the WSe 2 devices exhibit Ohmic behavior down to 0.25 K and at low enough excitation voltages to avoid current-heating effects. Additionally, the high-quality hBNencapsulated WSe 2 devices in ideal Hall-bar geometry enable us to accurately determine arXiv:2012.02873… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 68 publications
3
22
1
Order By: Relevance
“…[8,9] More specifically, carrier transport within a channel is significantly influenced by the localized state commonly known as the trap states at the 2D channelgate dielectric interface by inducing transport through interface of the WSe 2 flake from ≈20 to 0.73 nm (monolayer), different from previous studies. [23,27,29] We carried out multifrequency capacitance-voltage (MFC-V) and transport measurements with temperatures ranging from 300 to 75 K to determine the effect of interface quality and correspondingly localized D t on MIT. Since MFC-V measurements carried out by applying different excitation frequencies (1 kHz to 1 MHz in this study) provide direct insight about localized D t , they are considered the most appropriate and powerful technique to analyze the channel-gate dielectric interface and its impact on device characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[8,9] More specifically, carrier transport within a channel is significantly influenced by the localized state commonly known as the trap states at the 2D channelgate dielectric interface by inducing transport through interface of the WSe 2 flake from ≈20 to 0.73 nm (monolayer), different from previous studies. [23,27,29] We carried out multifrequency capacitance-voltage (MFC-V) and transport measurements with temperatures ranging from 300 to 75 K to determine the effect of interface quality and correspondingly localized D t on MIT. Since MFC-V measurements carried out by applying different excitation frequencies (1 kHz to 1 MHz in this study) provide direct insight about localized D t , they are considered the most appropriate and powerful technique to analyze the channel-gate dielectric interface and its impact on device characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7,22] Thus, it is difficult to correctly identify the origin of MIT in a 2D material system when both carrier-carrier interactions and a large amount of localized trap states (≈10 13 cm -2 eV -1 ) induced from the channel and channel-gate dielectric interface effects come into play.In the past, some efforts have been made to explain the MIT in 2D MoS 2 , [23][24][25][26] ReS 2 , [27] CuInSe, [28] and WSe 2 . [29] However, most of these studies were limited to a certain channel thickness. Although a few studies have reported MIT in 2D materials, [23,[26][27][28][29][30] how localized D t interplays near a transition point with varying thickness of 2D flakes remains unclear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The inset in Figure 2a shows that activation energy vanishes at V G = −21 V, further confirming the MIT point. 24 Below the MIT point, the conductivity increases with decreasing temperature, thus indicating metallic behavior (Δσ/ΔT < 0), as shown in Figure 2b. However, above the MIT point, the conductivity decreases with decreasing temperature, thereby showing the insulating phase (Δσ/ΔT > 0) as can be seen in Figure 2b.…”
Section: ■ Introductionmentioning
confidence: 89%